Pengadaan Barang/Jasa Pemerintah dalam Perspektif Hukum Administrasi Negara - Syafar, Irfan; Ramadhan, Realizhar Adillah Kharisma (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the implementation of government procurement of goods and services from the perspective of State Administrative Law (HAN) and to identify challenges and strategies for improving the integrity of the procurement system. The method used is an empirical legal approach with qualitative analysis, combining normative studies of regulations and empirical studies through observation and interviews with government agencies. Data analysis using data analysis techniques is carried out qualitatively. The results of the study show that although procurement regulations are quite comprehensive, practices in the field still face obstacles such as weak supervision, potential deviations, and limited human resource capacity and digital infrastructure. The implementation of the e-procurement system has been proven to increase transparency and efficiency, but its success is highly dependent on the integrity of the implementers and institutional support. Consistent law enforcement and strengthening of oversight mechanisms and public participation are the main keys to realizing clean and accountable procurement. This study emphasizes that procurement reform must be carried out holistically by integrating legal, institutional, technological, and bureaucratic cultural aspects to improve governance of government procurement of goods and services